FAKTOR – FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - EDDY JONI; TONI GUNAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to obtain empirical evidence regarding the effect of return on assets, leverage, sales growth, firm size, capital intensity, firm age and institutional ownership on tax avoidance in manufacturing companies listed on Indonesia Stock Exchange. This study uses 77 manufacturing companies that are listed consistently on Indonesia Stock Exchange from 2017 to 2019. The sample selection technique in this study is purposive sampling and uses secondary data obtained from the official website of Indonesia Stock Exchange. The data analysis method used in this study is multiple regression. The results of this study indicate that sales growth and capital intensity have a significant effect on tax avoidance, while other independent variables such as return on assets, leverage, firm size, firm age and institutional ownership do not have a significant effect on tax avoidance